Analysis and risk assessment of vinyl chloride emitted from aerosol products. Issue 4 (21st March 2023) - Sugaya, Naeko; Inoue, Kaoru; Tahara, Maiko; Kawakami, Tsuyoshi
Abstract: The objectives of this study were to develop a novel analytical method for quantifying vinyl chloride (VC) emitted from aerosol products, to provide analytical data on VC in aerosol products, and to evaluate consumer VC exposure by aerosol products. Our quantitative method involves absorbing VC into dimethyl sulfoxide and analyzing it using headspace gas chromatography/mass spectrometry. The correlation coefficients of the VC calibration curves were ≥ 0.9994 in the range of 0.16–80 µg/mL VC standard gases, which were prepared under either nitrogen or emission gases containing dimethyl ether or liquid petroleum gas. VC concentrations in these emission gases were calculated using a VC calibration curve from standard gases prepared under nitrogen; they were within ± 10% of the actual concentrations. We analyzed 39 household aerosol products; VC concentrations of 0.095, 0.098, and 0.28 μg/L were detected in three polyvinyl chloride spray paints. Consumer VC inhalation exposure level was estimated through an exposure scenario, and the hazard quotient was confirmed to be very low when comparing the exposure level with a cancer risk level of 10 −5 for inhaled VC. These results suggest that the human health risk from VC in spray paint was low.